2021
DOI: 10.1186/s12889-021-10359-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self-rated health among an older Tibetan population in a Chinese plateau area: analysis based on the conceptual framework for determinants of health

Abstract: Background Self-rated health (SRH) has been frequently used in population health surveys. However, most of these studies only focus on specific factors that might directly affect SRH, so only partial or confounding information about the determinants of SRH is potentially obtained. Conducted in an older Tibetan population in a Chinese plateau area, the aim of our study is to assess interrelationships between various factors affecting SRH based on the conceptual framework for determinants of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In this study, we observed statistical differences in the prevalence of chronic diseases across different ethnic groups, ages, education levels, employment status, household wealth, and self-rated health status(P<0.05) (Table 1). The risk of chronic disease increased over the age (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) 4).…”
Section: Association Between Demographic Characteristics Health Statu...mentioning
confidence: 99%
“…In this study, we observed statistical differences in the prevalence of chronic diseases across different ethnic groups, ages, education levels, employment status, household wealth, and self-rated health status(P<0.05) (Table 1). The risk of chronic disease increased over the age (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) 4).…”
Section: Association Between Demographic Characteristics Health Statu...mentioning
confidence: 99%
“…Physical activity comprehensively considered the occupation, transportation, household, and leisure time of participants [32]. Sleep disorders were assessed by early awakening, difficulty in falling asleep, drug-assisted sleep and poor sleep, and any positive one was defined as sleep disorder [33].…”
Section: Assessment Of Outcome and Other Covariatesmentioning
confidence: 99%
“…Previous studies were mostly concerned with health-related individual and family factors such as medical, biological or hereditary conditions; psychosocial, demographic, social and economic conditions; and healthy lifestyle (HLS). [9][10][11][12][13][14] State-level health status factors were only considered when the analyses were concerned with cross-country differences. For example, the level of democratic governance was found to have a positive association with health.…”
Section: Open Accessmentioning
confidence: 99%
“…To be healthy has multidimensional factors,8 with complex roles at different levels (individual, families, community and state). Previous studies were mostly concerned with health-related individual and family factors such as medical, biological or hereditary conditions; psychosocial, demographic, social and economic conditions; and healthy lifestyle (HLS) 9–14. State-level health status factors were only considered when the analyses were concerned with cross-country differences.…”
Section: Introductionmentioning
confidence: 99%